Evaluation of Food Service Management on the Satisfaction of Diabetes Mellitus Patients - Sofiadila, Aulia; Harris Rambey; Aya Sofia Diaz; Desri Meriahta Br. Girsang (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: The prevalence of Diabetes Mellitus in Aceh has increased, reaching 1.68% in 2018 compared to 1.3% in 2013. In Bireuen District, the number of diabetes mellitus patients receiving healthcare services also rose in 2022, with 11,300 patients compared to 11,218 in 2021 (Riskesdas, 2018).Objective: This study aims to evaluate food service in relation to the satisfaction of diabetes mellitus patients. Research method: This research is a descriptive qualitative study. Informants include the head of the nutrition installation, ward nutritionists, food service staff, DM patients, and their families. Data were collected through a combination of in-depth interviews, focus group discussions, and observations. Data analysis was conducted manually using content analysis without software, and data validity was ensured through triangulation. Results: The average food waste of patients remains above 20%. Although the prescribed diet is generally appropriate, changes often occur based on doctors' recommendations. Delays in meal delivery still occur, especially during menu cycles involving chicken and meat. Menu variations follow a 10-day cycle; however, some ingredients are occasionally unavailable due to stock shortages.Conclusion: The satisfaction of DM patients with food service at RSUD dr. Fauziah, Bireuen District, still needs improvement, particularly regarding high food waste, delays in meal delivery, limited availability of ingredients in the menu cycle, and suboptimal communication by food service staff with patients.